Effects of Combined Ohmic–Infrared Cooking Treatment on Microbiological Inactivation of Meatballs. Issue 1 (3rd November 2015) - Sengun, Ilkin Yucel; Icier, Filiz; Kor, Gamze
Abstract: The effectiveness of combined ohmic–infrared cooking system on the microbiological quality of meatballs was studied. In the first step, samples were precooked in an ohmic heater at 15.26 V/cm. In the second step, ohmically precooked samples were processed in the infrared heater for the final cooking purpose at different combinations of heat fluxes (3.7, 5.7, 8.5 kW/m 2 ), application distances (10.5, 13.5, 16.5 cm) and application times (4, 8, 12 min). The effects of infrared process conditions on total mesophilic aerobic bacteria (TMAB) counts of meatball samples were investigated. TMAB counts of meatball samples were reduced, ranging between 1.96 and 4.50 logarithmic units, depending on infrared process conditions used. Mold and yeast, S taphylococcus aureus, C lostridium perfringens, S almonella spp., L isteria monocytogenes and E scherichia coli O157:H7 were not detected in the treated meatball samples. The effects of different infrared cooking conditions both on cooking value and pasteurization value were also determined. These results demonstrate the considerable potential for the application of ohmic–infrared combination cooking process to the meatballs. Practical Applications: Meat is a nutritious substrate for the growth of microorganisms and is highly susceptible to spoilage. The raw meat contaminated with pathogenic microorganisms is one of the main sources of foodborne illness. During conventional cooking, the interior region may not heat sufficiently and pathogens could survive in the product, unless the meat products have been properly heat‐treated. Therefore, there is a potential need for alternative cooking technologies, which provide a valuable tool to reduce the risk of pathogen growth in the products while shortening the treatment time. In this study, the combination of ohmic and infrared heating technologies was used for cooking of the meatball.